Concordance Between Physician’s Clinical Diagnostic Terminology and ICD‑10 on Surgical Patient Medical Records - Khumaira, Nurul Fitri; Yastori; Kader, Shaola Syafrullah (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: The accurate use of medical terminology in clinical diagnosis is crucial for proper disease classification, coding accuracy, and reliable health data reporting. However, inconsistencies remain due to non-standard terminology and abbreviations that do not comply with the International Classification of Diseases (ICD-10).Objective: This study aims to evaluate the conformity of physicians’ diagnostic terminology with ICD-10 and with the hospital’s official abbreviation guidelines.Methods: This descriptive quantitative cross-sectional study was conducted from March to July 2025 at RSKB Ropanasuri Padang. A 96 surgical patient medical records from 2024 were selected through simple random sampling. Diagnostic data were evaluated using a conformity checklist based on ICD-10 Volume 1 and 3 and the hospital’s standardized abbreviation guidelines.Results: : The results showed that not all diagnoses complied with ICD-10 terminology or abbreviation guidelines. Common discrepancies included non-standard abbreviations, inconsistent anatomical terminology, and non-specific terms such as “tumor” without further details.Conclusion: Concordance Physician’s diagnostic terminology with ICD-10 and Abbreviation guidelines remains inadequate. Strengthening standard operating procedures, enhancing clinician training in ICD-10 nomenclature, and establishing more structured coder–clinician communication are essential to ensure valid and reliable health data.